2012
DOI: 10.1080/01635581.2012.687425
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Vitamin A Preloading Reduces Colorectal Cancer Metastatic Multiplicity in a Mouse Xenograft Model

Abstract: Previous research in our laboratory showed that retinol inhibited all-trans retinoic acid (ATRA)-resistant human colon cancer cell invasion via a retinoic acid receptor (RAR)-independent mechanism in vitro. The objective of the current study was to determine if dietary vitamin A supplementation inhibited metastasis of ATRA-resistant colon cancer cells in a nude mouse xenograft model. Female nude mice (BALB/cAnNCr-nu/nu, n=14 per group) consumed a control diet (2400 IU retinyl palmitate/kg diet) or a vitamin A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 44 publications
0
17
1
Order By: Relevance
“…Park et al have shown that retinol inhibits the growth and the invasion of colon cancer cells in vitro, [18][19][20] and that retinol does not induce apoptosis. However, retinol does affect cell cycle progression in synchronized colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al have shown that retinol inhibits the growth and the invasion of colon cancer cells in vitro, [18][19][20] and that retinol does not induce apoptosis. However, retinol does affect cell cycle progression in synchronized colon cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Park et al have shown that retinol inhibits the growth and the invasion of RA-resistant colon cancer cells in vitro. [18][19][20] In addition, we have shown that retinol is a more potent suppressor of cancer cell growth and adhesion of several cancer cell lines including refractory cancers (pancreatic, gallbladder, breast, or prostate cancer, and cholangiocarcinoma) than RA or RP in vitro. 21) Most vitamin A actions other than vision are considered to be mediated by RA, which can regulate gene expression by binding to nuclear RA receptors (RAR) or retinoid X receptors (RXR).…”
Section: -7)mentioning
confidence: 99%
“…37) Previous studies have shown that retinol inhibits the growth and the invasion of RA-resistant colon cancer cells in vitro and in vivo. [19][20][21][22] Retinol reduces invasiveness by decreasing the activity and mRNA expression of matrix metalloprotease and phosphatidylinositol 3-kinase (PI3K) activity, and not through RAR/RXR pathways. In addition, we have shown that retinol may act in refractory cancer cells through mechanisms that are distinct from RAR/RXR.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] In addition, we have shown that retinol is a potent suppressor of cancer cell growth and adhesion of several cancer cell lines including refractory cancers in vitro. 23) Retinol suppresses the growth of human gallbladder cancer NOZ C-1 cells to a greater extent than RA, while RP shows no effects.…”
mentioning
confidence: 99%
“…In addition, vitamin A is stored in the liver as retinyl esters. Elevated intestinal lumen and hepatic concentrations of retinol have been attained by dietary vitamin A supplementation (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%